Geographies, Genders and Geopolitics of James Bond - Funnell, Lisa. author. aut Link
XI, 242 p. 20 illus. in color.
Keywords: ‘As a Bond scholar and fan, this book opened my eyes to new ways of understanding the Bond films. Funnell and Dodds, both renowned scholars in their own fields, have combined disciplinary perspectives to provide an insightful and highly original analysis of the Bond franchise. This is a very welcome addition to the world of Bond scholarship that will also be valuable for students of geopolitics, gender and cultural studies.’ - James R. Chapman, Professor of Film Studies, University of Leicester, UK. ‘This book constitutes a significant, well-argued and accessible addition to the field of Bond scholarship, demonstrating a high level of research and discussion. The authors’ approach and methodology offer a fresh and relevant perspective on the subject that will interest both the academic and general reader.’ -Daniel O'Brien, Film tutor in Medical Humanities, University of Southampton, UK. ‘Brilliantly perceptive and beautifully written – Geographies, Genders, and Geopolitics of James Bond is a remarkable achievement. Funnell and Dodds develop a unique and highly original intersectional reading of Bond’s globe-trotting adventures, which are shown to reflect, reproduce, and disrupt dominant geopolitical and affective imaginaries over time. Not only will you never see Bond the same way again – this book will challenge your preconceptions about the relationship between geopolitics, security, and popular culture’ - Nick Vaughan-Williams, Professor of International Security, University of Warwick, UK. ‘With so many books about James Bond treading the same tired ground, does the worldneed another Bond related book? The answer is a resounding YES! Funnell and Dodds have produced one of the most original studies of how Bond has changed the world landscape. It is scholarly yet accessible for anyone wanting to know more about Bond’s relationship to gender and geopolitics. For those teaching a class on Bond, you now have an additional textbook that helps us understand the meaning of Bond today. Drink a martini, have a seat, and enjoy Geographies, Genders, and Geopolitics of James Bond!’ - Robert G. Weiner, Popular Culture Librarian Texas Tech University, UK. This book discusses the physical and political geographies of the Bond film franchise and how they inform our reading of 007 as a hero. To survive and succeed in a dangerous world, Bond has to feel, move and think his way through and past threats and dangers. This account is a truly immersive journey into Bond’s worlds. Lisa Funnell is Assistant Professor in the Women’s and Gender Studies Program at the University of Oklahoma, USA. Klaus Dodds is Professor of Geopolitics at Royal Holloway, University of London, UK. .